Trends in the prevalence of anorexia nervosa among individuals under 45 years in China, 1992–2021: an age-period-cohort analysis - Tian, Jun; He, Yuheng; Chen, Yiyi; Tang, Zheng; Zhou, Yongzhao (Frontiers in Public Health, 2025)
ObjectiveThis study aims to analyze the temporal trends in the incidence and prevalence of anorexia nervosa (AN) in China from 1992 to 2021, focusing on age, period, and cohort effects, in order to provide evidence for the prevention and control of anxiety-related disorders.MethodsData on the incidence and prevalence of anorexia nervosa in China were obtained from the Global Burden of Disease Study 2021. Joinpoint regression analysis was employed to assess trends over time, while an age-period-cohort (APC) model was used to estimate the net effects of age, period, and cohort variables.ResultsFrom 1992 to 2021, the incidence and prevalence of anorexia nervosa among individuals under 45 years in China showed a general upward trend. The annual percent change (APC) for incidence was 1.29%, and for prevalence was 0.31%, with both rates consistently higher in females than in males. Age effects revealed that the highest incidence and prevalence occurred between ages 10 and 25, followed by a gradual decline. Period effects demonstrated a consistent upward trend across the total population. Cohort analysis indicated an intergenerational increase in the risk of anorexia nervosa.ConclusionThe incidence and prevalence of anorexia nervosa among individuals under 45 years in China have increased steadily from 1992 to 2021. This growing disease burden, with marked age and gender disparities, highlights the urgent need for targeted interventions, especially among adolescents and women.